Strategic Scientific and Medical Writing The Road to Success - Joubert, Pieter H. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
A document may be based on accurate medical and scientific information, follow guidelines precisely, and be well written in clear and correct language, but may still fail to achieve its objectives. The strategic approach described in this book will help you to turn good medical and scientific writing into successful writing. It describes clearly and concisely how to identify the target audience and the desired outcome, and how to construct key messages for a wide spectrum of documents. Irrespective of your level of expertise and your seniority in the pharmaceutical, regulatory, or academic environment, this book is an essential addition to your supporting library. The authors share with you many years of combined experience in the pharmaceutical and academic environment and in the writing of successful outcome-driven documents.